Santarpanotha Nidana Questionnaire Evaluating and Designing - Shwetarani; Nandesh Mohan P (AYUSHDHARA, 2023)
The word Sanatapana is satisfying the desire or over nourishment or restoration. Prithvi and Aap Mahabhuta are contributing for Santarapana and it leads to increase in Kapha Dosha and Meda and Mamsa dhatu. If the person indulges in intake of Nidanas like Snigdha, Madhura, Guru, Picchila Ahara practicing these for longer duration causes Santarapaniya Vyadhis such as Prameha, Pidaka, Kotha, Kandu etc in this study Sanatarapana questionnaire are prepared based on the above-said Nidana. According to the Samanya Vishesha Siddhanta, Samana guna acts as Vriddhi karana. So here, there are five steps in the research process of designing and validating a questionnaire in the field of clinical research. There are different types of research among them, this questionnaire is used in a survey study i.e., in observational Research. Here an attempt is made based on the review of previously proved fundamentals of Ayurveda with the current lifestyle.